1974
DOI: 10.1021/ja00828a047
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins. 40. Highly stereoselective total syntheses of prostaglandins via stereospecific sulfenate-sulfoxide transformations. 13-cis-15.beta.-Prostaglandins E1 to prostaglandins E1

Abstract: 14) Two Pyrex tubes, the first containing l a and the second containing l b , in equimolar amount, and both containing equimolar amounts of sensitizer (benzophenone), were irradiated in a merry-goround apparatus to ensure equal absorption of light, then analyzed for the amount of 3 and 4 produced. The low yield of the products and their instability to the reaction conditions limit the accuracy of this experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…It also provided a mechanistic basis for designing new synthetic transformations, the most important of which was the Evans method for synthesizing allylic alcohols from allylic sulfoxides by reducing the intermediate sulfenate . Although Mislow had shown that the equilibrium favors the sulfoxide, the Evans reaction proceeds to completion because reduction of the sulfenate removes it from the equilibrium as soon as it forms …”
Section: Introductionmentioning
confidence: 99%
“…It also provided a mechanistic basis for designing new synthetic transformations, the most important of which was the Evans method for synthesizing allylic alcohols from allylic sulfoxides by reducing the intermediate sulfenate . Although Mislow had shown that the equilibrium favors the sulfoxide, the Evans reaction proceeds to completion because reduction of the sulfenate removes it from the equilibrium as soon as it forms …”
Section: Introductionmentioning
confidence: 99%
“…However, previous inversions in prostaglandin intermediates (10) as well as earlier work by Evans et al (1 1-13) with tert-butyl substituted cyclohexanes indicated that in these sterically biased systems the allylic sulfoxide rearrangement proceeded across the equatorial face of the cyclohexylidene ring to give predominantly the equatorial alcohol. These studies revealed that the transition state for these Can (a) CH2 = CHMgBr, THF, O°C, 1 h, 99% (b) n-BuLi, THF, 0°C then -78"C, PhSCI, 1.5 h, 21°C, 12 h, 46% (c) (MeO)3P, MeOH, 65°C.…”
Section: !' -/-mentioning
confidence: 92%
“…The [2,3]-sigmatropic rearrangement involving allylic sulfoxides and allylic sulfenates has been applied extensively to the synthesis of prostaglandins and related products. The pioneering report by Untch and colleagues that described the straightforward double isomerization (geometry of alkene and configuration of C-15 alcohol) set the stage for the use of this rearrangement in the field . Treatment of Z allylic alcohol 524 with p -TolSCl gave sulfenate 525 , which underwent [2,3]-rearrangement to produce allylic sulfoxide 526 (Scheme ).…”
Section: Mislow–braverman–evans Rearrangements In the Synthesis Of Bi...mentioning
confidence: 99%